(untitled) (Fiep Bulletin - online, 2014)
The happenings and the experiences of the professional life, which involve the teachers’ daily lives, since they begin their career until the moment they retire or abandon the teaching practice, can provoke a tension in the work environment, interfering directly in the pedagogical interventions, in the teaching socialization, in the commitment and in the responsibilities assumed by these people in the educational context. The study had as its main objective to investigate the level of professional satisfaction of the Physical Education teachers. Its sample was constituted by 13 teachers working with public high school night classes in Chapecó/SC. To collect and analyze the data, we used the "Technique DIP-EF" and the "Evaluation of Content of the Technique DIP_EF" (GONZÁLEZ & LÓPEZ, 2002). The results show that 54% of teachers present a level inclined towards professional satisfaction; 31% present contraditory satisfaction and 15% present more dissatisfaction than satisfaction. The main intrinsic reason of satisfaction is the motivation demonstrated by students during the classes taught. The extrinsic reasons that give basis to dissatisfaction in the teachers’ work were: the professional devaluation, the lack of recognition on the part of other professionals and by society, the structure offered by the school, followed by low salaries. The intrinsic reasons of dissatisfaction pointed out by teachers were: the lack of interest and of motivation on the part of students, and the lack of incentive to sports and other physical activities on the part of professionals in the area. Through the studies presented, one can conclude that, despite the most part of the professionals present themselves as being satisfied, an expressive percentage of the group shows contraditory satisfaction or professional dissatisfaction; that the intrinsic reasons give basis to the teachers’ satisfaction and the extrinsic reasons to the dissatisfaction in the school environment.